Students’ perceptions of teacher support in Finnish basic education - Suvi Kanerva; Risto Hotulainen; Sanna Oinas (Cogent Education)
This study aimed at validating the Finnish translation of the teacher subscale of the Child and Adolescent Social Support Scale (CASSS; Malecki et al.) and providing current results regarding Finnish students’ teacher support. Participants (N = 51,105) in the study come from a large-scale nationally representative research project called Schooling, teaching, and well-being in the school community during the COVID-19 pandemic, which offers a comprehensive scientifically grounded view of Finnish basic education students’ perceptions of social support from their teachers. The methods used in this study are based on multivariate analyses. The study concluded that the translated subscale is a valid and reliable tool for measuring Finnish 4th–9th grade students’ perceptions of teacher social support, and that the scale created in the US context works in a Nordic setting. Contrary to previous findings, the results show that boys perceived the highest levels of support from their teachers. The study provides new insights by investigating the perceptions of Finnish non-binary students, suggesting that non-binary students perceive the lowest levels of teacher support. The results indicate a strong need for further studies on the social support of non-binary students.